A Case Study Exploring the Reading Engagement of Middle Grades English Learners. Issue 3 (16th March 2017) - Protacio, Maria Selena
Abstract: This study investigates the reading engagement of four middle school English learners in their English or English as a Second Language classroom. Students with high levels of reading engagement are those who (a) are motivated to read, (b) use strategies when reading, (c) use reading as a way to construct meaning from texts, and (d) participate in social interactions around reading (Guthrie & Wigfield, 2000). This study focuses on all four aspects of reading engagement and explores whether there are any additional components that should be considered with English learners' reading engagement. Data included in this case study research include semi-structured interviews, field notes from classroom observations, comprehension assessments, reading activity inventories, and student artifacts. Findings from this case study research indicate that all four components are essential to consider with English learners' reading engagement. Results of this study also reveal that English learners' identities are an essential component of their reading engagement.